Impact of the Black School Market in Some Primary Schools in Kinshasa on School Performance. (Global Journal of Human-Social Science, 2023)
In the process of transforming circulating resources the producers and consumers direct and indirect of the offers of black school markets constitute a panacea for raising the level of the quality of the teaching-learning process long decried by educational actors Competition in the current school market is a function not only of the quantity of finished products but also and above all of its quality This is why an observation on the black or clandestine school market which reached a peak in the primary schools of Kinshasa deserved a sustained study Several practices emerge from this market with a more positive influence on school performance The study aimed to explain the impact of the black school market on the academic performance of students After survey and analysis of data collected from 148 teachers and administrators the results showed that almost all of the respondents practice the black school market and it has a positive impact on school performance but generates additional costs with a monthly average of 50 530 FC or 25 3 While the average hourly volume is one forty minutes
Keywords: impact; black school market; school; school performance